Perbandingan antara CT Score dan Saturasi Oksigen pada Pasien COVID-19 di Rumah Sakit UKI Tahun 2021 - Patricia Roulin Elizabeth (Faculty of Medicine, Universitas Andalas, 2023)
Coronavirus disease 2019 (COVID-19) is an infectious disease that has causedpandemic effects on world demographics. It is caused by severe acute respiratorysyndrome coronavirus 2 (SARS-CoV 2). COVID-19 can attack various organs,especially the lungs. The first time a COVID-19 case was discovered in Indonesiawas announced on March 2, 2020. The number of casesspread rapidly in Indonesia.The objective of this study is to findout the comparison of CT scores and oxygensaturation of COVID-19 patients at UKI Hospital in East Jakarta. This study usesa cross-sectional design using medical records and data analysis using Mann–Whitney. Based on the result of the study, high CT-Score causes low OxygenSaturation, Furthermore, there is a relationship between CT Score and oxygensaturation of COVID- 19 patients at UKI Hospital in East Jakarta with a p-valueof 0.05.